Profile of Ectopic Pregnancy at Kathmandu Model Hospital - Pradhan, HK; Dangal, G; Karki, A; Shrestha, R; Bhattachan, K (Nepal Journal of Obstetrics and Gynaecology, 2016)
Aims: The study was done to analyze the epidemiology, diagnosis and treatment aspect of patients with ectopic pregnancy at Kathmandu Model Hospital. Methods: This was a retrospective study of patients with ectopic pregnancy who received treatment at Kathmandu Model Hospital from January 2008 to September 2015. Data were analyzed from patient records and discharge summary. Delivery number was obtained from maternity record. Results: There were 61 cases of ectopic pregnancy with the hospital incidence of 1.46%. Highest number of patients 20 (32.79%) were in the age range of 28-32 years. Most of the patients were nullipara 22 (36.06%) or with parity two 20 (32.79%). Some risk factors were found in 29 (47.54%) cases. The commonest risk factor was pelvic inflammatory disease in 12 (19.67%). All presented with pain abdomen, 48 (78.68%) had per vaginal bleeding, 17 (27.87%) presented in shock. Cervival excitation was present in 38 (62.29%). Urine for pregnancy test was positive in all and 37 (60.66%) had ultrasonography. Ten (16.39%) patients underwent emergency laparoscopic surgery and 40 (65.57%) had emergency laparotomy. Salpingectomy was required in 53 (86.89%) cases. The average hospital stay was 5 days. Conclusions: The study showed that ectopic pregnancy could occur at any reproductive age without obvious risk factors. Although not all patients gave history of amenorrhoea, pain abdomen was present in all.